Exploring Tuberculosis Riskscapes in a Papua New Guinean 'Hotspot'. (September 2022) - Jops, Paula; Kupul, Martha; Trumb, Richard Nake; Cowan, John; Graham, Stephen M.; Bell, Stephen; Majumdar, Suman; Nindil, Herolyn; Pomat, William; Marais, Ben; Marks, Guy; Vallely, Andrew J.; et al.
This article explores socio-spatial dimensions of risk and how they can enhance understanding of a high burden tuberculosis (TB) context in the South Fly District of Papua New Guinea. We report on select findings from a qualitative study that included 128 semi-structured in-depth interviews and 10 focus group discussions with a wide range of South Fly District community members. Using the conceptual framework of 'riskscapes' to examine emic perspectives on risk, space and practice, we map key elements of TB riskscapes on Daru Island, South Fly District, along with solutions for navigating through these riskscapes. Overcrowding, lack of water, sanitation and hygiene, as well as food insecurity and undernutrition, were identified as common elements within participants' riskscapes, that compounded upon each other to create the perception of an assemblage of risk favourable to TB transmission.